The Form and Function of Dialectical Cinécriture in Beckett's Company. Issue 2 (September 2016) - Flynn, Deirdre
Abstract : In this essay I argue that throughout Company Beckett adopts the technique of dialectical montage, which he encountered in the work of Eisenstein, to create a radically new autographical form of transmedial cinécriture . I suggest that this cinécriture enables Beckett not only intellectually to communicate the provisionality of self to readers, but also bodily to engage readers in a dialectical dynamic by which they directly experience the self for what it really is: an always-provisional synthesis in an always-provisional time and space. I begin the essay by considering the motivating factors that may have compelled Beckett to combine elements of film, radio, and prose in the late 1970s, after decades of resisting transmedial adaptations. I then examine the form and function of dialectical montage and constructive editing in Company . Next, I outline the form and function of intellectual montage and deep-focus space-time throughout the text and, in particular, in the penultimate watch sequence. Finally, I elaborate upon the ethical implications of the dialectic that these techniques set in motion.